MOESI-prime: preventing coherence-induced hammering in commodity workloads - Loughlin, Kevin; Saroiu, Stefan; Wolman, Alec; Manerkar, Yatin A.; Kasikci, Baris (49th International Symposium on Computer Architecture (ISCA), 2022)
Prior work shows that Rowhammer attacks—which flip bits in DRAM via frequent activations of the same row(s)—are viable. Adversaries typically mount these attacks via instruction sequences that are carefully-crafted to bypass CPU caches. However, we discover a novel form of hammering that we refer to as coherence-induced hammering, caused by Intel's implementations of cache coherent non-uniform memory access (ccNUMA) protocols. We show that this hammering occurs in commodity benchmarks on a major cloud provider's production hardware, the first hammering found to be generated by non-malicious code. Given DRAM's rising susceptibility to bit flips, it is paramount to prevent coherence-induced hammering to ensure reliability and security in the cloud. Accordingly, we introduce MOESI-prime, a ccNUMA coherence protocol that mitigates coherence-induced hammering while retaining Intel's state-of-the-art scalability. MOESI-prime shows that most DRAM reads and writes triggering such hammering are unnecessary. Thus, by encoding additional information in the coherence protocol, MOESI-prime can omit these reads and writes, preventing coherence-induced hammering in non-malicious and malicious workloads. Furthermore, by omitting unnecessary reads and writes, MOESI-prime has negligible effect on average performance (within ±0.61% of MESI and MOESI) and average DRAM power (0.03%-0.22% improvement) across evaluated ccNUMA configurations.